Evolution and the fall - Cavanaugh, William T., 1962-; Smith, James K. A., 1970- (Grand Rapids, MI, W.B. Eerdmans Publishing Company, 2017)
What does it mean for the Christian doctrine of the Fall if there was no historical Adam? If humanity emerged from nonhuman primates?as genetic, biological, and archaeological evidence seems to suggest?then what are the implications for a Christian understanding of human origins, including the origin of sin? Evolution and the Fall gathers a multidisciplinary, ecumenical team of scholars to address these difficult questions and others like them from the perspectives of biology, theology, history, Scripture, philosophy, and politics. - back of book.
Introduction. Beyond Galileo to Chalcedon : resources for reimagining evolution, human origins, and the Fall / William T. Cavanaugh, James K.A. Smith -- I. Mapping the questions. Human origins : the scientific story / Darrel R. Falk -- In Adam all die? : questions at the boundary of Niche construction, community evolution, and original sin / Celia Deane-Drummond -- What stands on the Fall? : a philosophical exploration / James K.A. Smith -- II. Biblical studies and theological implications. Reading Genesis 3 attentive to human evolution : beyond concordism and non-overlapping magisteria / J. Richard Middleton -- "Adam, what have you done?" : New Testament voices on the origins of sin / Joel B. Green -- The mystery of Adam : a poetic apology for the traditional doctrine / Aaron Riches -- III. Beyond "origins" : cultural implications. Being all we should have been and more : the Fall and the quest for perfection / Brent Waters -- On learning to see a fallen and flourishing creation : alternate ways of looking at the world / Norman Wirzba -- IV. Reimagining the conversation : faithful ways forward. The fall of the Fall in early modern political theory : the politics of science / William T. Cavanaugh -- Is science-religion conflict always a bad thing? : Augustinian reflections on Christianity and evolution / Peter Harrison.
Includes bibliographical references and indexes.
Keywords: Bible and evolution; Evolution; Evolution (Biology) -- Religious aspects -- Christianity; Eden; Religion and science